Barriers to Trade in Financial and Insurance Services : Evidence from the United Kingdom - Podpiera, Jiri. (Washington, D.C. : International Monetary Fund, 2021)
Distance, as a proxy for trade barriers, is found in many studies to matter even for weightless cross-border financial investments and lending, possibly due to the presence of information asymmetries. Its importance is tested in this paper using exports of all five broad categories of the U.K.'s financial and insurance services. No trade barriers are found for the bulk of the U.K.'s exports. Trade barriers are confirmed only for interest-bearing activities - being in line with available results in the literature. The positive effect of EU membership appears to be small. Notwithstanding the uncertainties, it suggests that post-Brexit disruptions of the U.K.'s export of financial and insurance services may be minor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Empirical Studies of Trade; Insurance; Micro Finance Institutions; Mortgages